Um modelo de gestão para prevenção da má utilização da web - Macedo, Ricardo Tombesi (2012)
Currently, the use of the Web in the workplace has provided new business models, reduced communication cost and agility in business processes. However, some side effects also arise, since it is estimated that 30-40% of employees taken improperly use of this technology. Among the improper activities are online shopping, games playing and access to pornography sites. Besides exposing the organization s network to computer virus, such behavior causes around of 54 billion dollars annually in lost productivity. From literature, we know the most widely used preventive approach to address this problem is the use of Internet Use Policies (PUI), that corresponds to specification guidelines for employers in determining how the Internet should be used in the workplace. Despite its widespread use, the application of PUI presents difficulties in relation to compliance with the specified guidelines and these guidelines have been applied directly on Internet access filters through Access Control Policies (PCA). By applying PCA, the granularity is a key factor to ensure the web use control, claiming by contextual attributes manipulation that offer fine granularity. However, fine granularity increases the cost of PCA management, mainly because the dynamic changing of web user needs. This work proposes a management model for prevents Internet bad usage in the workplace by using context-based PCAs combined to a police continuous management framework to prevent the PCAs become obsolete. To facilitate the translation of needs to PCAs a software were developed to allow administrators without specific technical knowledge to continuous manage fine-grained PCAs. A case study has developed to validate the applicability of the model in a production environment. The result was the enhancement of a wireless network usage in an educational public institution.